Quality Assurance Parameters as Predictors of Teachers’ Motivation in Kwara State Public Junior Secondary Schools - Abiola, Yusuf Abubakar (American Journal of Social Sciences and Humanities, 2022)
The study examined quality assurance parameters as predictors of teachers’ motivation in public junior secondary schools in Kwara State. The study adopted the descriptive survey research design of correlation type. The population for this study comprised 5149 teachers of public junior secondary schools in Kwara State. The sample comprised of 640 teachers selected using the multistage sampling technique. A self-developed and validated research instrument titled “Quality Assurance Parameters and Motivation Questionnaire” (QAPMQ) was used to collect information with a reliability coefficient of 0.85. The result showed that teachers in public junior secondary schools in Kwara State had a moderate level of motivation (52.3%). The further showed that quality assurance parameters are significant predictors of teachers’ motivation (72.6% (Adj. R2= 0.726); and each of the quality assurance parameters of human resource maintenance (Beta= 0.704, t= 25.132) and data management (Beta= 0.366, t= 13.101) had significant predictions to teachers’ motivation, while funding was not significant (Beta= -0.275, t= -9.638) in Kwara State public junior secondary schools. Therefore, it was recommended that Kwara State government should not relent its efforts and continue to work collaboratively with Non-Governmental Organizations (NGOs), philanthropists, and other stakeholders in the education sector to ensure its assurance parameters are continued and appropriately used in stimulating teachers’ motivation in the State public secondary schools.